Role of Ag nanoparticles embedded on optical, photoluminescence and elastic properties of samarium magnesium borotellurite glass system - Zalamin, S. N. F.; M. Zaid, M. H.; Matori, K. A.; A. Karim, M. K.; Yusof, N. N.; Iskandar, S. M.; Hisam, R.; Azlan, M. N. (Elsevier, 2023)
This paper reports the effect of silver nanoparticle (Ag NPs) on the optical, photoluminescence and elastic properties of samarium magnesium borotellurite (TBMSm) glass system with nominal composition of (58-x) TeO2–30B2O3–10MgO-2Sm2O3-xAg NPs, where x = 0.0, 0.1, 0.3, 0.5, 1.0 and 2.0 mol% synthesized via melt quenching method. To achieve the goals, the glasses are analyzed using densitometer, X-Ray Diffraction, Transmission Electron Microscopy, UV–Visible Spectroscopy, Photoluminescence, CIE Chromaticity analysis and ultrasonic testing. The density is decreased from 4.162 to 4.310 g/cm3 with the incorporation of Ag NPs. The absence of a prominent peak in the XRD area demonstrated that the glasses were amorphous. TEM shows that the diameter size of Ag NPs is increasing from 40.94 nm to 367.70 nm with the rise of Ag NPs concentration. The indirect transitions have an optical band gap of 2.618–2.800 eV, while direct transitions have an optical band gap of 2.839–2.897 eV. The refractive index is ranging between 2.453 and 2.508 while the Urbach energy, ΔE, is in the range of 0.338–0.391 eV. Photoluminescence measurement shows the occurrence of four emission intensity at different wavelength, with the highest red emission intensity at 605 nm. The analysis of colour chromaticity indicated that the colour coordinates were situated in the red-orange region. When Ag NPs were incorporated into the glass sample, there was an inconsistent pattern observed in the values of the longitudinal, shear, Young’s, and bulk moduli, which ranged from 59.17 to 70.84 GPa, 20.70–24.21 GPa, 50.97–60.02 GPa, and 31.57–41.77 GPa, respectively.